2011
DOI: 10.1371/journal.pone.0023749
|View full text |Cite
|
Sign up to set email alerts
|

Preschoolers' Precision of the Approximate Number System Predicts Later School Mathematics Performance

Abstract: The Approximate Number System (ANS) is a primitive mental system of nonverbal representations that supports an intuitive sense of number in human adults, children, infants, and other animal species. The numerical approximations produced by the ANS are characteristically imprecise and, in humans, this precision gradually improves from infancy to adulthood. Throughout development, wide ranging individual differences in ANS precision are evident within age groups. These individual differences have been linked to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
313
3
10

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(358 citation statements)
references
References 35 publications
19
313
3
10
Order By: Relevance
“…Moreover, of studies that have examined the relation between AMS and SNS tasks at different timepoints, few if any include control for the outcome at time 1 (e.g., Libertus et al, 2011;Mazzocco et al, 2011;Wang et al, 2016). Inclusion of this control is crucial because it allows one to genuinely predict growth in the outcome.…”
Section: Reconciling Current Results With Previous Workmentioning
confidence: 99%
“…Moreover, of studies that have examined the relation between AMS and SNS tasks at different timepoints, few if any include control for the outcome at time 1 (e.g., Libertus et al, 2011;Mazzocco et al, 2011;Wang et al, 2016). Inclusion of this control is crucial because it allows one to genuinely predict growth in the outcome.…”
Section: Reconciling Current Results With Previous Workmentioning
confidence: 99%
“…For example, used displays of 2500ms for 3-year-olds, 1200ms for 4-, 5-and 6-year olds, and 750ms for adults, and Mazzocco et al (2011b) used display times of 1200ms and 2500ms for the two age groups in their study, combining the data into a single analysis. Our findings indicate that this analysis strategy may be flawed, and that Weber fractions derived from tasks with different display times are not comparable.…”
Section: Methodological Implicationsmentioning
confidence: 99%
“…Several recent studies have shown that individuals' ANS acuities are correlated with achievement in symbolic mathematics (e.g. Gilmore, McCarthy & Spelke, 2010;Libertus, Feigenson & Halberda, 2011;Mazzocco, Feigenson & Halberda, 2011a, 2011b; but see Inglis, Attridge, Batchelor & Gilmore, 2011;Price, Palmer, Battista & Ansari, 2012), lending credence to the suggestion that the ANS is implicated in the development of symbolic mathematics competence.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Bonny & Lourenco, 2013;Castronovo & Göbel, 2012;Halberda, Ly, Willmer, Naiman, & Germine, 2012;Inglis et al, 2011;Libertus et al, 2011Libertus et al, , 2012Lyons & Beilock, 2011;Mazzocco et al, 2011a;Piazza et al, 2010;Price et al, 2012;Sasanguie, Göbel, Moll, Smets, & Reynvoet, 2013). It makes the INDEXING THE APPROXIMATE NUMBER SYSTEM 5 theoretical assumption that the ANS operates according to the Weber-Fechner law (e.g.…”
mentioning
confidence: 99%